Designing and Optimization of Lipid-Based Nanocarriers for Safer and Effective Oral Delivery of Tizanidine Hydrochloride (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The oral route is widely favored for drug delivery due to its simplicity. However, after oraladministration, the effectiveness of tizanidine hydrochloride (TZN) is limited due to its low solubility and increasedmetabolism. The present study investigates the utility of nanostructured lipid carriers (NLCs) as an oral formulationfor TZN to boost its therapeutic effectiveness. Materials and Methods: TZN-loaded NLCs were prepared by thesolvent evaporation method using glyceryl monostearate and oleic acid as solid and liquid lipids, respectively, whilethe combination of tween 80 and poloxamer 188 was used as surfactants. The formulation optimization was carriedout using a Box–Behnken design taking particle size and entrapment efficiency as response variables. The optimizedformulation underwent evaluation for particle size, polydispersity index (PDI), ζ-potential, morphological studies,entrapment efficiency, permeability, and drug release characteristics. Results: The final optimized formulationexhibited all the necessary attributes, including a particle size of 320.6 ± 13.86 nm, PDI of 0.376 ± 0.031, a zetapotential of −25.8 mV, and entrapment efficiency of 78.33% ± 1.96%. In vitro release studies have also demonstratedsubstantial drug release profiles, highlighting the potential of NLCs for enhanced drug delivery with extendedreleaseprofiles. Conclusion: The above findings signify that the current optimization model can be used for thedevelopment of NLCs for safer and effective oral delivery of TZN which have all the necessary pharmaceuticalattributes and may be a promising avenue for its safer and more effective delivery for such drugs.